Advanced high resolution x-ray diagnostic for HEDP experiments. Issue 1 (December 2018) - Faenov, A.; Pikuz, T.; Mabey, P.; Albertazzi, B.; Michel, Th.; Rigon, G.; Pikuz, S.; Buzmakov, A.; Makarov, S.; Ozaki, N.; Matsuoka, T.; Katagiri, K.; et al.
Abstract High resolution X-ray imaging is crucial for many high energy density physics (HEDP) experiments. Recently developed techniques to improve resolution have, however, come at the cost of a decreased field of view. In this paper, an innovative experimental detector for X-ray imaging in the context of HEDP experiments with high spatial resolution, as well as a large field of view, is presented. The platform is based on coupling an X-ray backligther source with a Lithium Fluoride detector, characterized by its large dynamic range. A spatial resolution of 2 µm over a field of view greater than 2 mm2 is reported. The platform was benchmarked with both an X-ray free electron laser (XFEL) and an X-ray source produced by a short pulse laser. First, using a non-coherent short pulse laser-produced backlighter, reduced penumbra blurring, as a result of the large size of the X-ray source, is shown. Secondly, we demonstrate phase contrast imaging with a fully coherent monochromatic XFEL beam. Modeling of the absorption and phase contrast transmission of X-ray radiation passing through various targets is presented.